Monetary policy, housing booms and financial (im)balances - Sandra Eickmeier; Boris Hofmann (European Central Bank (ECB), 2010)
This paper uses a factor-augmented vector autoregressive model (FAVAR) estimated on U.S. data in order to analyze monetary transmission via private sector balance sheets, credit risk spreads and asset markets in an integrated setup and to explore the role of monetary policy in the three imbalances that were observed prior to the global financial crisis: high house price inflation, strong private debt growth and low credit risk spreads. The results suggest that (i) monetary policy shocks have a highly significant and persistent effect on house prices, real estate wealth and private sector debt as well as a strong short-lived effect on risk spreads in the money and mortgage markets; (ii) monetary policy shocks have contributed discernibly, but at a late stage to the unsustainable developments in house and credit markets that were observable between 2001 and 2006; (iii) financial shocks have influenced the path of policy rates prior to the crisis, and the feedback effects of financial shocks via lower policy rates on property and credit markets are found to have probably been considerable.
Keywords: E52; E44; C3; E3; E43; 330; asset prices; factor model; financial crisis; housing; monetary policy; private sector balance sheets; Geldpolitik; Geldpolitische Transmission; Immobilienpreis; Private Verschuldung; Kreditrisiko; Risikoprämie; Finanzkrise; Schätzung; USA